Clinical patterns of juvenile idiopathic arthritis in Zambia - Chipeta, James (BioMed Central, 2013)
BACKGROUND: Juvenile idiopathic arthritis (JIA) is a heterogeneous group of disorders with different disease manifestations among various populations. There are few reports of JIA among indigenous Africans especially sub-Saharan Africa. We present herein the clinical patterns of JIA encountered at a tertiary hospital in Lusaka, Zambia. METHOD: Hospital records of patients with a diagnosis of chronic arthritis with onset at the age of 16 years or less presenting to University Teaching Hospital, Lusaka, Zambia for the periods 1994–98 and 2006–2010 were retrospectively reviewed and reclassified as Juvenile Idiopathic Arthritis (JIA) based on the International League of Associations for Rheumatology (ILA R) JIA diagnostic criteria. RESULTS: In total, 126 patients with chronic arthritis of onset at age 16 years or less were evaluated over these periods at the hospital. Of these, 85 could further be analyzed by ILAR JIA criteria but 7 (8.24%) were HIV seropositive and were assessed separately. The average age at disease onset among the 78 JIA patients was 8.70 years (range: 1–15 years) with average age at first visit to hospital being 11.3 years (range: 2 to 25 years) and with a female to male ratio of 1.2:1. Polyarticular rheumatoid factor negative JIA, at 34.62%, was the most frequent type of chronic arthritis encountered. Oligoarthritis was found in 32.05% while 11.54% and 14.10% were polyarticular rheumatoid factor positive and systemic JIA, respectively. Enthesitis-related arthritis was found in 6.41% and only 1.28% were determined to have psoriatic arthritis among this population. CONCLUSION: JIA is predominantly a polyarticular rheumatoid factor negative disease in Zambia. Late presentation is an issue with major implications for educational input and resource acquisition. There is need to elucidate the genetics and environmental factors of JIA in this region.